Occipital Cortical Calcifications in Cerebral Amyloid Angiopathy. Issue 5 (5th April 2021) - Rasing, Ingeborg; Voigt, Sabine; Koemans, Emma A.; van Zwet, Erik; de Kruijff, Paul C.; van Harten, Thijs W.; van Etten, Ellis S.; van Rooden, Sanneke; van der Weerd, Louise; van Buchem, Mark A.; van Osch, Matthias J.P.; Greenberg, Steven M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Cortical calcifications have been reported in patients with cerebral amyloid angiopathy (CAA), although their prevalence and pathophysiology are unknown. We investigated the frequency of calcifications on computed tomography, their association with intracerebral hemorrhage (ICH) and their coexistence with a striped pattern of the occipital cortex reflecting microcalcifications on ultra-high-field 7T-magnetic resonance imaging in Dutch-type hereditary CAA (D-CAA) and sporadic CAA. Methods: We included D-CAA mutation carriers with a proven APP (amyloid precursor protein) mutation or ≥1 lobar ICH and ≥1 first-degree relative with D-CAA and sporadic CAA patients with probable CAA according to the modified Boston criteria. D-CAA carriers were regarded symptomatic when they had a history of symptomatic ICH. We assessed the presence, location, and progression of calcifications and their association with ICH and the striped occipital cortex. Results: We found cortical calcifications in 15/81 (19% [95% CI, 11–29]) D-CAA mutation carriers (15/69 symptomatic and 0/12 presymptomatic) and in 1/59 (2% [95% CI, 0–9]) sporadic CAA patients. Calcifications were all bilateral located in the occipital lobes. In 3/15 (20%) of the symptomatic D-CAA patients the calcifications progressed over a period up to 10 years. There was evidence of an association between cortical calcifications and new ICH development (hazard ratio, 7.1 [95% CI, 0.9–54.9], log-rank P =0.03). In 7/25 D-CAA symptomatic carriers in whom a 7T-magnetic resonance imaging was performed, a striped pattern of the occipital cortex was present; in 3/3 (100%) of those with calcifications on computed tomography and 4/22 (18%) of those without calcifications. Conclusions: Occipital cortical calcifications are frequent in D-CAA but seem to be rare in sporadic CAA. Their absence in presymptomatic carriers and their association with ICH might suggest that they are a marker for advanced CAA. Cortical calcifications on computed tomography seem to be associated with the striped occipital cortex on 7T-magnetic resonance imaging which may possibly represent an early stage of calcification.